Análisis socio-económico de los comerciantes de las plazas y mercados del cantón Pujilí provincia de Cotopaxi en el período 2014 - 2015 - Aguayo García, Mayra Azucena (2015)
Nowadays, the lack management is notorious in merchants of shoppining places and markets in Pujilí of Cotopaxi province, reason why it was necessary to develop a socio-economic research about mentioned group; several investigative techniques were used to carry out this research, they were the survey and interview. It was observed a low economic level in the merchants of these sites by inadequate organization of trade at this town, it was necessary to analyze their status and observe the current situation how they live. According to the results of the investigation, it is proposed a reorganization of posts, better waste management and healthiness, to ensure that the situation of traders improves.